MORPHOLOGICAL RELATIONSHIPS AND CONVERSION FACTORS IN SPINY LOBSTER PANULIRUS POLYPHAGUS (HERBST) FROM THE NORTHWEST COAST OF INDIA - Kagwade, P V (Indian Journal of Fisheries, 2011)
Conversion factors have been determined for 5 sets of variables, namelycarapace length and total length, abdominal weight and total weight, total lengthand total weight, total length and abdominal weight and carapace length andabdominal weight. The relationship between the first 2. sets of variables was foundto be linear and the other 3 sets, exponential. Carapace is longer in malethan in female. The female has a shorter carapace and hence a longer as well asheavier abdomen, whereas the total weight is more in male than in female.